Penerapan Manajemen Pembelajaran di Program Studi Teknik Mesin Politeknik Raflesia - Mirliani (Jurnal Pendidikan Vokasi Raflesia, 2021)
One of the goals of learning is to initiate, facilitate, and increase the intensity and quality of learning in students. Learning Management helps lecturers, students and educational institutions to achieve lecture goals in general or in particular. The purpose of this study was to determine learning planning, implementation of learning, and evaluation / assessment of learning outcomes in the Mechanical Engineering Study Program at the Raflesia Polytechnic. This type of research is descriptive qualitative, data collection techniques by means of observation, interviews, and documentation. The data obtained were analyzed by data reduction steps, data presentation, and drawing conclusions. The results showed that the learning planning in the Mechanical Engineering Study Program of the Raflesia Polytechnic had been carried out well, this was because before starting the lecture at the beginning of the semester all lecturers Course instructors are required to prepare lecture materials and submit them to the study program.